Identification of Clay Element Content in Fabric Dyeing Process Using X-Ray Fluorescence Spectrometry - Nengsih, Reni Fitria; Rifai, Hamdi; Dwiridal, Letmi; Akmam, Akmam; Fauzi, Ahmad; Yusrizal, Yusrizal (Universitas Negeri Semarang, 2022)
Clay in West Sumatra has been used as a natural dye for batik, so the batik is known as clay batik. The dyeing of the cloth is done by boiling and soaking the clay together with the cloth for 10 days. The color of the fabric is caused by certain elements present in the clay. Currently, no one has investigated the changes in elemental content due to the dyeing process. This research aims to investigate the changes in the concentration of the elements that affect the color of the fabric. Samples were taken from 4 areas, namely Solok, Sijunjung, Lima Puluh Kota, and Pesisir Selatan with a total of 8 samples, of which 4 samples were measured before the staining process and 4 more samples after the staining process. Changes in the elemental content of clay were investigated using X-Ray Fluorescence (XRF). The results of the study showed changes in the content of the dominant element, namely Al, Si, and Fe contained in samples CL-PYKLN 2A and CL-TJG GDG 210422. While the samples CL-PSB-SJJ 210421 and CL-SPPS 1 210314 the change in the concentration of the elemental content was not too significant. The elements that cause colored cloth are all elements in clay, but the dominant element in coloring cloth is Fe.